HR Competencies, Strategic Roles, and HRM Effectiveness : Examining the Role of Generation Y in India’s Construction Industry - Somu, Subbulakshmi; Ali, Noor Azman; Islam, Md Asadul; Watabe, Motoki (Prabandhan: Indian Journal of Management, 2025)
Purpose : This study explored the influence of human resource competencies on human resource management (HRM) effectiveness, focusing on Generation Y human resource professionals in India’s construction industry. The purpose was to examine the relationships between HR competencies, strategic HR roles, and HRM effectiveness, focusing on the mediating role of strategic HR roles and the moderating effect of generational differences. Methodology : In this study, HR competencies were considered as the independent variable, strategic HR roles as the mediating variable, HRM effectiveness as the dependent variable, and Generation Y as the moderating variable. A quantitative approach was used, collecting data from 386 HR professionals using a structured questionnaire, and the data were analyzed using SMART PLS. Findings : The findings revealed that HR competencies in business knowledge, HR delivery, and change management positively influenced the performance of strategic HR roles. These roles, in turn, contributed to HRM effectiveness. However, the study found no significant moderating effect of Generation Y on the relationship between HR competencies and strategic roles. Strategic HR roles mediated the relationship between competencies and HRM effectiveness, highlighting that competencies alone were insufficient without their application in strategic roles. Practical Implications : Organizations should prioritize the universal development of HR competencies by ensuring that training and development programs are accessible and beneficial to HR professionals of all age groups. This approach promoted continuous learning and development, enabling HR professionals to engage in strategic roles. However, this study was not free from limitations and allows scope for future researchers, as discussed in this paper. Originality : The study’s originality lay in its application of role theory and its focus on the Indian construction industry, providing insights into the strategic role of HR professionals in a non-Western context.